Screening, identification, and degradation characteristics of 3-methylindole degrading bacteria - Hu, Hong; Li, Lei; Gao, Feng; Diao, Wentao; Ma, Huan; Feng, Fei; Quan, Shujing; Xiang, Lingyun; Zhang, Xiujiang (Frontiers in Environmental Science, 2022)
3-Methylindole is a major component of organic pollutants in livestock compost, which can contribute to the deterioration of the environment in livestock farms and their surrounding areas. This study demonstrates that using microorganisms to degrade 3-methylindole is an effective method for energy conservation and environmental protection. The microbe capable of efficiently degrading 3-methylindole was isolated and screened from fecal samples. The isolated bacteria were identified as Acinetobacter oleivorans after morphological characterization and 16S rRNA sequencing. This project demonstrated that 3-methylindole was completely degraded under optimal conditions (initial concentration of 3MI: 100 mg/L, 30°C, pH8.0, and shaking at 160 rpm for 48 h). N2-Acetyl-L-ornithine, Phenylacetaldehyde, Phenylacetic acid, Indole-3-carboxylic acid, and Indole-3-carboxaldehyde were the primary metabolites of this degradation process. This study provides a theoretical foundation for other microbe-mediated environmental remediation approaches as well as a basis for future work to apply bacteria that degrade 3-methylindole for the purification of polluted environments.It has a promising application in the control of malodorous gas pollution in the large-scale livestock and poultry breeding industries.